The effects of 4 weeks normobaric hypoxia training on microvascular responses in the forearm flexor. Issue 11 (3rd June 2019) - Fryer, S.; Stone, K.; Dickson, T.; Wilhelmsen, A.; Cowen, D.; Faulkner, J.; Lambrick, D.; Stoner, L.
ABSTRACT: Intermittent exposure to hypoxia can lead to improved endurance performance. Currently, it is unclear whether peripheral adaptions play a role in improving oxygen delivery and utilization following both training and detraining. This study aimed to characterize skeletal muscle blood flow (mBF), oxygen consumption (mV̇O2 ), and perfusion adaptations to i) 4-weeks handgrip training in hypoxic and normoxic conditions, and ii) following 4-weeks detraining. Using a randomised crossover design, 9 males completed 30-min handgrip training four times a week in hypoxic (14% FiO2 3250m altitude) and normoxic conditions. mBF, mV̇O2 and perfusion were assessed pre, post 4-weeks training, and following 4-weeks detraining. Hierarchical linear modelling found that mV̇O2 increased at a significantly faster rate (58%) with hypoxic training (0.09 mlO2 ·min −1 · 100g −1 per week); perfusion increased at a significantly (69%) faster rate with hypoxic training (3.72 μM per week). mBF did not significantly change for the normoxic condition, but there was a significant increase of 0.38 ml· min −1 · 100ml −1 per week (95% CI: 0.35, 0.40) for the hypoxic condition. During 4-weeks detraining, mV̇O2 and perfusion significantly declined at similar rates for both conditions, whereas mBF decreased significantly faster following hypoxic training. Four weeks hypoxic training increases the delivery and utilisation of oxygen in the periphery.